RANCANG BANGUN ALAT MONITORING KUALITAS UDARA DIAREA PENGOLAHAN LIMBAH RUMAH SAKIT - Dhiki Meirza Alfath; Wahyudi, Bayu; Mohammad Rofi’i (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2025)
Decreased air quality caused by air pollution can cause respiratory problems if inhaled for a long period of time. The absence of air quality monitoring equipment in the waste management area means that workers do not know the level of air pollution that occurs in the hospital area. This research aims to create an Air Quality monitoring system in the Hospital Waste Processing Area. The air that will be monitored is Methane, CO, Alcohol and NH4. Data on temperature, humidity, methane gas, alcohol gas, CO gas and NH3 gas are sent via ESP32 to the smartphone and sent directly to Google Sheet in real time, so that data acquisition from this tool is stored properly. Indoor measurements showed that Methane Gas showed an average of 40.9 ppm, then around the IPALL area Methane Gas rose to 81.0, this was because methane gas around the IPALL area had increased. Indoor measurements show that CO gas shows an average of 3 ppm, then around the IPALL area, CO gas increases to 165 ppm, this is because CO gas around the IPALL area has increased. Indoor measurements show that Alcohol Gas shows an average of 1 ppm, then around the IPALL area Alcohol Gas increases to 969 ppm, this is because Alcohol gas around the IPALL area has increased. Indoor measurements show that NH4 gas shows an average of 4 ppm, then around the IPALL area Methane Gas increases to 986 ppm, this is because methane gas around the IPALL area has increased